Analysis of Fire and Explosion Consequences in Accidents Involving Premium Gasoline Tanker Trucks - Ridwan, Mochamad Maulana; Ramadhani, Adhitya Ryan (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2024)
A series of accidents frequently occur in the fuel transport process in Indonesia, resulting in explosive incidents. This study explores the implications of fires and explosions in Premium Fuel tanker truck accidents in Bintaro Permai, focusing on identifying hazard zones and the extent of possible damage. The aim is to map the hazard zones and assess the potential level of damage due to fire and explosion of Premium fuel tanker trucks in the area. Quantitative methods were used with pool fire modelling and the TNT (Trinitrotoluene) method. This study showed that the pool fire modelling found the highest heat flux value in the pool with a pool diameter of 20 m and a distance to the receptor of 11 m, with a value of 14.85 kW/m2. Meanwhile, in modelling the explosion using the TNT Method, an overpressure value of 175.75 kPa was found for a volume of 20,000 L and a distance of 50 m.